Rebuilding trust between Silicon Valley and Washington - Segal, Adam, 1968- (CSR (New York, N.Y.) ;, 2017)
"Cyber threats to the United States are escalating in sophistication and magnitude, but mistrust between Washington and Silicon Valley continues to stymie progress on cybersecurity. In a new Council Special Report, Adam Segal examines the security risks exacerbated by the divide between government and the technology community and offers policy recommendations to help restore trust"--Publisher's web site.